2020
DOI: 10.1002/pds.5008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid monitoring of health services utilization following a shift in coverage from brand name to biosimilar drugs in British Columbia—An interim report

Abstract: Purpose: We explored changes in health services utilization associated with the Biosimilars Initiative introduced in British Columbia on May 27, 2019. To maintain drug coverage, the policy requires users of originator infliximab or etanercept to transition to biosimilar versions. We present a three-month interim analysis of this initiative. Methods: We conducted a rapid monitoring analysis to evaluate changes in health services utilization three months after the policy was introduced compared with a threeyear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This study had several limitations. 25 First, we did not test hypotheses and hence are unable to support or reject the null hypothesis of no difference in health services utilization after the policy was launched. As such, we did not adjust for patient characteristics, and differences in patient characteristics could lead to changes in clinical practice and health services utilization.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study had several limitations. 25 First, we did not test hypotheses and hence are unable to support or reject the null hypothesis of no difference in health services utilization after the policy was launched. As such, we did not adjust for patient characteristics, and differences in patient characteristics could lead to changes in clinical practice and health services utilization.…”
Section: Discussionmentioning
confidence: 96%
“…The launch of the Biosimilars Initiative was followed by real-time monitoring of its impacts. 23 – 25 Some impacts were expected, such as an increase in visits to specialists during the 6-month transition period or immediately thereafter because of patient–physician consultations needed to monitor a switch to a biosimilar. 10 , 14 Also, a shift in health services utilization was expected beginning Mar.…”
mentioning
confidence: 99%
“…This includes Manitoba (tiered reimbursement), 29 British Columbia (switching of patients from specific innovator to biosimilar products), 30 and most recently Alberta (tiered reimbursement and switching to be implemented by January 2021). 31 These policy changes are anticipated to, and have already indicated that they will, improve biosimilar uptake 32 and should be considered in Ontario and other jurisdictions in Canada, as well as globally to further improve uptake and reduce costs.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted rapid monitoring of health services utilization [ 25 , 26 ] using a prospective cohort study design and administrative data from the BC Ministry of Health. The data included population-based, province-wide information on prescriptions filled in all community pharmacies, diagnoses recorded in visits to physicians and other providers, hospital and emergency department records, and medical services registration data.…”
Section: Methodsmentioning
confidence: 99%
“…These methodologies require significant resources and are limited to a single analysis, which is often delayed. The aim of this rapid monitoring analysis was to detect signals of intended and unintended impacts on health services utilization over a one-year period following the launch of the Biosimilars Initiative for patients treated with originator etanercept [ 25 , 26 ]. Our study was designed to detect potential signals of unintended negative impacts in an entire population, and not to accept or reject a hypothesis of harm in the presence of a sampling error.…”
Section: Introductionmentioning
confidence: 99%